2011
DOI: 10.1094/pdis-11-10-0836
|View full text |Cite
|
Sign up to set email alerts
|

Newly Discovered Natural Hosts of Tomato chlorosis virus in Costa Rica

Abstract: Tomato chlorosis virus (ToCV) is an emerging whitefly-transmitted crinivirus (2). In Costa Rica in 2007, ToCV was detected in field-grown and greenhouse tomato (Solanum lycopersicum L.) plants causing symptoms of severe yellowing and foliar chlorosis (1). To identify alternative hosts that may serve as virus reservoirs, 78 samples were collected from multiple species of common weeds growing adjacent to tomato nurseries in the Cartago Province, where ToCV was previously identified, during the autumn of 2008 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…, 2006; Wintermantel & Wisler, 2006; Trenado et al. , 2007; Solórzano‐Morales et al. , 2011), including some important crops, ornamentals and weeds.…”
Section: Introductionmentioning
confidence: 99%
“…, 2006; Wintermantel & Wisler, 2006; Trenado et al. , 2007; Solórzano‐Morales et al. , 2011), including some important crops, ornamentals and weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies involving different crops have also shown the importance of weeds as potential virus reservoirs to infect crops that are economically important and contributing to disease occurrence during the growing season, and also to virus dissemination (Ali et al, 2012;Papayiannis et al, 2011;Papayiannis et al, 2012;Solórzano-Morales et al, 2011;Asala et al, 2014). Additionally, weeds can still withstand drought in the field, and survive in the absence of preferred hosts, becoming an important initial source of virus inoculum, which can be spread not only to commercial crops, but also to infect other weed plants after harvesting periods (Asala et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…En Costa Rica, durante décadas, los begomovirus identificados se establecían en los cultivos y las arvenses no tenían un papel relevante para los investigadores (Hilje et al, 2001). En la actualidad, esa idea ha cambiado y ahora se reconoce que estas plantas podrían funcionar como puentes entre los virus, el vector y los cultivos cercanos (Solórzano- Morales et al, 2011;Castro et al, 2013;Vargas-Asencio et al, 2013).…”
Section: Familiaunclassified